ASSESSMENT OF WOOL CHARACTERISTICS OF MENGALI SHEEP OF BALOCHISTAN - M. M. Tariq; M. A. Bajwa; K. Javed; M. Rafeeq; M. A. Awan; N. Rashid; A. Waheed; S. Amin; M. A. Khan; F. A. Bukhari (Journal of Animal and Plant Sciences, 2013)
The study was carried out to establish the environmental factors' influence on the wool production as well as analyzed the wool quality parameters of Mengali sheep. The wool production data on 3150 offspring sired by 38 rams in four flocks at three locations over a period of 5 years (Jan. 2005 to Dec. 2009) were included in the analysis. Data thus collected was subjected to statistical analysis by standard methods of analysis of variance. The average autumn fleece weight (AFW), spring fleece weight (SFW) and combined fleece weight (CFW) were 1.35±0.82, 1.17±0.75 and 2.50±0.64kg, respectively. Animal model was fitted with shearing season and location of flocks as fixed and animal as random effects. The heritability estimates for AFW, SFW, and CFW were 0.19±0.03, 0.22±0.06 and 0.18±0.04, respectively. Wool traits of sheep (n=90) were found as: coarse wool with diameter 41.62±4.57μ; black (85%) and white (15%) in color, true fiber 65.07±5.06%, modullated fiber 11.2±3.2%, Kemp 10.1±2.79%, heterotype 21.0±1.06% and staple length 6.25±1.12cm. Season of shearing and location of flocks had significant effects (P0.05) for fleece traits. Mengali wool characteristics are best suited for carpet manufacturing but color would be a limitation. These findings suggested that Mengali sheep wool production and quality can be improved through selection, management, and favorable environment.
Keywords: Wool traits; environmental factors; genetic parameters; Mengali sheep